2011
DOI: 10.1111/j.1365-2265.2010.03920.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life is less impaired in adults with congenital adrenal hyperplasia because of 21-hydroxylase deficiency than in patients with primary adrenal insufficiency

Abstract: HRQoL in CAH is only mildly impaired and significantly less than in PAI patients. Differences between PAI and CAH in HRQoL suggest relevant modulating factors of HRQoL other than hormone replacement therapy itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 35 publications
5
55
1
5
Order By: Relevance
“…However, there are no studies on personality traits in patients with PAI. To date, studies in patients with PAI have demonstrated impaired QoL (9,10,11,12,13,14,15), and a higher risk for the development of affective disorders such as depression or bipolar disorder (16). The QoL impairments in patients with PAI have been attributed, at least in part, to intrinsic imperfections of hormone replacement therapy (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no studies on personality traits in patients with PAI. To date, studies in patients with PAI have demonstrated impaired QoL (9,10,11,12,13,14,15), and a higher risk for the development of affective disorders such as depression or bipolar disorder (16). The QoL impairments in patients with PAI have been attributed, at least in part, to intrinsic imperfections of hormone replacement therapy (12).…”
Section: Introductionmentioning
confidence: 99%
“…I undersøkelser av helserelatert livskvalitet er det ulike resultater, men de største studiene, fra Norge, Storbritannia og Tyskland, viser signifikant lavere livskvalitet enn i den øvrige befolkningen (3,12,18).…”
Section: Helserelatert Livskvalitetunclassified
“…Current data on HRQoL in adult patients with 21-OHD shows conflicting results [11][12][13][14], however the most recent studies showed impaired HRQoL also in 21-OHD patients [15][16][17].…”
mentioning
confidence: 97%
“…For medical treatment of 21-OHD standard medications are hydrocortisone (HC), prednisolone (PR) and dexamethasone (DX) [16,18]. Since those glucocorticoids have a different biological strength, dosage for PR and DX were converted into milligrams of hydrocortisone equivalent (PR was converted 1 to 5 to HC, DX 1 to 70 to HC) [19,20].…”
Section: Subjectsmentioning
confidence: 99%